Tape casting of dielectric ALN substrate for microelectronic applications - Long, Yi. (2008)
The objective of thois project was to develop high performance dielectric AIN multilayered substrate for microelectronics applications using cost-effective starting powders, to obtain a combination of low dielectric constant and reduced density with an improved thermal conductivity, closer CTE match with silicon and high mechanical strength.